2020
DOI: 10.1186/s12944-020-01223-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential preventive and protective perspectives of different spice powders and their mixtures in rat model

Abstract: Background: The spices based dietary interventions are in lime light among the scientific community owing to their promising therapeutic perspective. The bioactive components in spices can be used to exert various health promoting functions in human body such as prompting weight loss, inhibit diet-induced obesity, hypercholesterolemia, hyperglycemia, allergies and various other maladies. In current study extraction and in vitro characterization of coriander seed (CS), black cumin seed (BCS) and fenugreek seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Also, cumin extracts decreased glycosylated hemoglobin in diabetic patients (28). It was proved that coriander seeds extract had hypoglycemic effect in streptozotocin-nicotinamide diabetic rat model in addition to its ability to increase insulin release from pancreas due to the presence of linalool and other active constituents (1) such as flavonoids, polyphenols, β-carotenoids, tannins, monounsaturated fatty acids and polyunsaturated fatty acids (29) which may contribute to the hypoglycemic effect of the formulated duqqa. Sesame seeds also contributed in the hypoglycemic effect of duqqa due to their content of some anti-diabetic lignans such as sesamin (30), phenolic compounds and dietary fibers (31).…”
Section: Discussionmentioning
confidence: 99%
“…Also, cumin extracts decreased glycosylated hemoglobin in diabetic patients (28). It was proved that coriander seeds extract had hypoglycemic effect in streptozotocin-nicotinamide diabetic rat model in addition to its ability to increase insulin release from pancreas due to the presence of linalool and other active constituents (1) such as flavonoids, polyphenols, β-carotenoids, tannins, monounsaturated fatty acids and polyunsaturated fatty acids (29) which may contribute to the hypoglycemic effect of the formulated duqqa. Sesame seeds also contributed in the hypoglycemic effect of duqqa due to their content of some anti-diabetic lignans such as sesamin (30), phenolic compounds and dietary fibers (31).…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, coriander seed extracts in ethanol and methanol were equally found exhibiting rich phytochemical profiles with high contents of phenolics and flavonoids, having high antioxidant potential. Flavonoids (quercetin and isoquercetin), polyphenols (rutin, caffeic acid derivatives, ferulic acid, gallic acid, and chlorogenic acid), carotenoids, and tannins were all present in the coriander seeds [1,45]. Extractions through assistance of different technologies have become a desirable environmentally friendly, economically viable, and highly bioactive yielding approach by which desired bioactives are released with preserved or improved efficacy.…”
Section: Analysis Of the Total Phenolic Contents (Tpc) Totalmentioning
confidence: 99%
“…Spices can be used to promote health in a variety of ways, including by helping people lose weight and preventing diseases including hypercholesterolemia, hyperglycemia, allergies, and obesity caused by food. The inclusion of numerous active phytochemicals, such as phenolics, flavonoids, carotenoids, vitamins, and minerals, is what gives spices their antioxidant potential [1][2][3]. Recently, there has been a resurgence of interest in using more natural items to improve fitness and health.…”
Section: Introductionmentioning
confidence: 99%
“…In stevia composition, there are irreplaceable amino acids, fatty acids and other favourable bioactive combinations including flavonoids, phenolic compounds, phytosterols, chlorogenic acids, and hydrocarbons (Wölwer-Rieck, 2012). Stevia is 200-400 times sweeter than fructose (Hameed et al, 2020). Recommended daily intake for steviol glycosides that is allowed to consume is 4 mg kg -1 of body mass (Swiader et al, 2019).…”
Section: Stevia and Steviol Glycosidesmentioning
confidence: 99%